Woman on the run - Tate, Sylvia; Lange, Arthur 1889-1956; Newman, Emil 1911-1984 (Film Noir Foundation, 2016)
"Nachdem ein Mann Zeuge eines Mordes geworden und untergetaucht ist, versucht seine ebenfalls bedrohte Ehefrau, ihn mit Hilfe der Polizei zu finden, ehe er von den Verbrechern getötet wird. Die dramatischen Ereignisse beheben sogar eine Ehekrise. Kriminalfilm mit origineller Handlung, intelligenten Dialogen und verhaltener Spannung." [filmdienst.de]
Original: USA 1950
special edition contents: brand new restoration of original 35mm vault elements by UCLA Film & Television Archive ; presented in High Definition Blu-ray (1080p) and Standard Definition DVD ; original mono audio (uncompressed PCM on the Blu-ray) ; optional English subtitles for the deaf and hard of hearing ; audio commentary by author, historian, and "noirchaeologist" Eddie Muller ; "Love is a rollercoaster: 'Woman on the run' revisited" - a new featurette on the making of the film, from script to noir classic, produced by Steven Smith and the Film Noir Foundation ; "A wild ride: restoring 'Woman on the run'" - a stranger-than-fiction document on the film's restoration, produced by Steven Smith and the Film Noir Foundation ; "Noir city" - a short documentary directed by Joe Talbot about the annual Noir City Film Festival presented by the Film Noir Foundation at San Francisco's historic Castro Theatre ; gallery featuring rare photographs, poster art and original lobby cards ; reversible sleeve featuring original and newly commissioned artwork by Matt Griffin
Keywords: Film